(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
When I first saw Kabir Das ji’s couplets, I was a high school student. At the time, I only studiedthem since they were required reading for the course. But during the second wave of the pandemic, whenmy environment was full of negativity and I was home alone, physically and mentally broken, I read KabirK Doha, and believe me, those couplets are a priceless gem for our generation. They offer a refreshinglyoptimistic perspective and a profound understanding of every facet of social life. Kabir’s devotion to theSupreme Power and his pursuit of enlightenment as a means of achieving love and philosophy arereflected in his writings. His poetry is evergreen since it touches on universal themes in the humancondition. Kabir Das ji’s ability to convey even the most complex ideas in terms that a layperson cangrasp is what makes his writings so accessible. His Several couplets have close ties to generallyapplicable behaviors that can be found in most competence dictionaries these dictionaries ofteninstruct readers on how to handle the art of living and life skills in the face of adversity.